2013
DOI: 10.1152/ajpgi.00193.2013
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ deficiency attenuates hepatic inflammation and fibrosis in a steatohepatitis model induced by a methionine- and choline-deficient high-fat diet

Abstract: Cytokines play important roles in all stages of steatohepatitis, including hepatocyte injury, the inflammatory response, and the altered function of sinusoidal cells. This study examined the involvement of a major inflammatory cytokine, interferon-γ (IFN-γ), in the progression of steatohepatitis. In a steatohepatitis model by feeding a methionine- and choline-deficient high-fat (MCDHF) diet to both wild-type and IFN-γ-deficient mice, the liver histology, expression of genes encoding inflammatory cytokines, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 83 publications
2
70
0
1
Order By: Relevance
“…Furthermore, in our down-regulated proteomic list, ISG20 and Mx1 protein, related to IFN signaling pathway, could be activated by STAT1. Moreover, IFN-γ deficiency could inhibit the inflammatory response of Kupffer cells, subsequently suppress HSCs activation and liver fibrosis35. Collectively, these experiments highlighted the critical role of STAT1 in the progression of liver fibrosis and indicated that suppression of STAT1 promote the reversion of activated HSCs.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, in our down-regulated proteomic list, ISG20 and Mx1 protein, related to IFN signaling pathway, could be activated by STAT1. Moreover, IFN-γ deficiency could inhibit the inflammatory response of Kupffer cells, subsequently suppress HSCs activation and liver fibrosis35. Collectively, these experiments highlighted the critical role of STAT1 in the progression of liver fibrosis and indicated that suppression of STAT1 promote the reversion of activated HSCs.…”
Section: Discussionmentioning
confidence: 78%
“…In our model, iron appears to be the trigger to cause the switch in polarization toward the M1 macrophages. In addition, CD8 T cells, which are one of the main producers of the potent cytokine, interferon ␥, were upregulated in the DI mice and have been implicated in the mechanisms leading to NASH (19,28). Additionally, DCs, a type of antigen-presenting myeloid immune cell population (characterized by the presence of CD11c marker, which was elevated in the livers of the DI mice), have also been proposed to contribute to the pathogenic process that governs NASH (12).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to IL-2, IL-4 and Opn were both elevated in liver tissue in a steatohepatitis model [58, 59]. While it is known that stimulation of B cells with IL-4 along with B-cell receptor engagement results in Opn production [6], the effect of Opn on IL-4 production is less clear.…”
Section: Discussionmentioning
confidence: 99%